Pengaruh Digital Marketing, Hedonic Motivation, Dan Materialisme Terhadap Impulsive Buying Pada Pelanggan Di Tiktok Shop - Sundy Wijaya; Muhyiddin Muhyiddin; Nia Aprilia (Institut Agama Islam Sumatera Barat, 2024)
Today's business world must be able to mobilize its resources effectively and efficiently in order to gain a competitive advantage in line with the development of the business world and competition for market share amidst increasingly fierce challenges and competition. To be able to survive in the face of competition, every business organization must be able to create a marketing plan, one of which must include a marketing mix that includes digital marketing. The aim of this research is to determine and evaluate the variables that influence customers' impulse purchases at TikTok stores. In this research, the sample used was one hundred respondents. This research uses quantitative methodology. Validity and reliability tests, multiple linear regression analysis, classical assumption tests, hypothesis tests (t tests), and coefficient of determination tests (R2) are the data analysis procedures used. The digital marketing variable (X1) partially has no negative and small influence according to the test results. The test findings of the hedonic motivation variable (X2) show a significant and partial beneficial effect. The test findings for the materialism variable (X3) are not statistically significant and only have a partial positive effect.